The challenges and contexts of the Lokaleng School Feeding Scheme in the North West Province, South Africa - Mkhombo, Bongi Bianca; Manka, Sheila Ngoh; Odhav, Kiran (The International Journal of Sociology of Agriculture and Food, 2024)
School Feeding Scheme Programmes (SFSP’s) are globally present, especially in countries where child poverty and malnutrition reflect a crisis. This paper evaluates the Lokaleng Primary School feeding scheme programme in Mmabatho, North West Province, South Africa. It serves one of the poorest villages in the area, with a mean of six dependents per family, most of whom are unemployed and uneducated. This has resulted in food insecurity in the village. After outlining the schemes’ challenges and benefits, the paper contextualises the schemes challenges by suggesting a more holistic and comprehensive approach focussed on the surrounding and extra-school conditions. A qualitative approach with in-depth one-on-one interviews was used. Study participants included schoolteachers, food suppliers (handlers), and parents of pupils. Data was analysed and presented using themes obtained from participants’ responses. Most respondents found that the feeding scheme does benefit pupils educationally, with increased school enrolments and attendance, and improved academic performance as Maijo (2018) concurs. Other studies however show mixed results when it comes to pupils’ physiological conditions, enrolment, or decreased dropout rates, and yet others show no correlation to such aspects. Difficult challenges remain in breaking the burden of poverty that families are exposed to, for which this paper gives some suggestions. One challenge identified in this study was the late delivery of food, resulting in irregular food supply to the school. The study makes baseline suggestions for the relevant government department, and for civics, to contribute to ensuring a more effective and sustainable school feeding programme.